Global trends in COVID-19 Alzheimer's related research: a bibliometric analysis - Cao, Chenjun; Li, Sixin; Zhou, Gaoya; Xu, Caijuan; Chen, Xi; Qiu, Huiwen; Li, Xinyu; Liu, Ying; Cao, Hui; Bi, Changlong (Frontiers in Neurology, 2023)
Background: The COVID-19 pandemic has significantly impacted public health, putting people with Alzheimer's disease at risk of significant harm. This topic intends to use bibliometric analysis methods to conduct in-depth research on the relationship between COVID-19 and Alzheimer's disease and to predict its development trend. Methods: The Web of Science Core collection was searched for relevant literature on Alzheimer's and Coronavirus-19 during 2019-2023 . We use a search query string in our advanced search. Using Microsoft Excel 2021 and VOSviewer software, statistical analysis of primary high-yield authors, research institutions, countries, and journals was performed. Knowledge networks, collaboration maps, hotspots, and regional trends can be analyzed with VOSViewer and CiteSpace . Results: During 2020-2023, 866 academic papers were published in international journals. United States, Italy, and the United Kingdom rank top three in the survey ;in terms of productivity, the top three schools were: Harvard Medical School, the University of Padua, and the University of Oxford; Bonanni, Laura from Gabriele d'Annunzio University (Italy)， Tedeschi, Gioacchino from University of Campania Luigi Vanvitelli (Italy)， Vanacore, Nicola from Natl Ctr Dis Prevent & Hlth Promot (Italy)， Reddy, P. Hemachandra from Texas Tech University (USA) and El Haj, Mohamad from University of Nantes (France) were the author who published the most articles; The Journal Of Alzheimers Disease is the journals with the most published articles; "COVID-19," "Alzheimer's disease," "neurodegenerative diseases," "cognitive impairment," "neuroinflammation," "quality of life," "neurological complications," has been the focus of attention in the last three years. Conclusion: The disease caused by the COVID-19 virus infection related to Alzheimer's disease has attracted significant attention worldwide. The major hot topics in 2020 were “Alzheimer's disease,”” covid-19,”” risk factors,”” care,” and “Parkinson's disease.” During the two years 2021 and 2022, researchers were also interested in" neurodegenerative diseases," "cognitive impairment," and" quality of life," which require further investigation.